Influence of the synthesis conditions on the characteristics and metal adsorption properties of the 3-(1,4-phenylenediamine)propylsilica xerogel - J. C. P. Vaghetti (Eclética Química, 2005)
The hybrid 3-(1,4-phenylenediamine)propylsilica xerogel was obtained starting from two differentorganic precursor quantity (5 and 8 mmol) to 22 mmol of TEOS, in the synthesis. The xerogel samples werecharacterized by using CHN elemental analysis, N2 adsorption-desorption isotherms, infrared thermalanalysis. The xerogel was used as metal sorbent for Cu2+, Cd2+ and Pb2+ in aqueous solution withconcentration range of 10-3 to 10-5 mmol l-1. The quantity of organic precursor added in the synthesisinfluences the characteristics of the xerogel as morphology and thermal stability, as well as the metaladsorption capacity.